Synthesis of decadeoxyribonucleotides containing N6-methyladenine, N4-methylcytosine, and 5-methylcytosine: recognition and cleavage by restriction endonucleases (nucleosides and nucleotides part 74). - Ono, A (1987)
The naturally-occurring modified bases, N6-methyladenine, N4-methylcytosine, and 5-methylcytosine were chemically introduced in place of the adenine or cytosine in the decadeoxyribonucleotides containing recognition sequences of Bgl II, Sau 3AI, Mbo I and Mfl I. The modified oligomers bind to the enzymes but the rates of cleavage by the enzymes are variable.